2018
DOI: 10.1007/s10396-018-0882-1
|View full text |Cite
|
Sign up to set email alerts
|

Flexor pollicis longus tendon rupture by sandwiched underlying volar locking plate and distal radius

Abstract: Flexor pollicis longus (FPL) tendon rupture is a major complication of volar locking plate fixation for distal radius fractures. The tendon rupture is usually caused by friction between the distal edge of the plate and the FPL tendon, and has been well detected recently with ultrasonography. Rarely, the volar locking plate itself entraps the FPL tendon, leading to its rupture. A 63-year-old man was consistently unable to flex his right thumb after previous surgery for a distal radius fracture at another hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…An FDS-IV transfer can also be used to restore opposition of the thumb in case of distal median nerve palsy or to restore finger and thumb extension in case of a radial nerve palsy (Boyes transfer) (Skie et al, 2010). Up to 12% of patients receiving a volar plate osteosynthesis for treatment of a distal radius fracture experience a rupture of the flexor pollicis longus (FPL) tendon (Drobetz and Kutscha-Lissberg, 2003;Uemura et al, 2018). Chronic FPL insufficiency can also result if a tendon injury is missed or if tendon repair has failed.…”
Section: Introductionmentioning
confidence: 99%
“…An FDS-IV transfer can also be used to restore opposition of the thumb in case of distal median nerve palsy or to restore finger and thumb extension in case of a radial nerve palsy (Boyes transfer) (Skie et al, 2010). Up to 12% of patients receiving a volar plate osteosynthesis for treatment of a distal radius fracture experience a rupture of the flexor pollicis longus (FPL) tendon (Drobetz and Kutscha-Lissberg, 2003;Uemura et al, 2018). Chronic FPL insufficiency can also result if a tendon injury is missed or if tendon repair has failed.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In one report, partially ruptured FPL tendon (around 40%) was primarily repaired during exploration 9 days after the first operation, 3 whereas totally ruptured FPL tendon was reconstructed by PL tendon grafting in the other report. 4 The most characteristic involvement of the FPL tendon between the plate and radial shaft is that the thumb motion is restricted immediately after surgery. Surgeons should be aware of this condition when the thumb motion was limited immediately after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with surgical treatment, radiocarpal joint stiffness (RJS) is a common postoperative complication following DRFs, which greatly influence patients' normal function [11,12]. Previous studies have investigated many postoperative complications following DRFs, such as tendon spontaneous rupture [13,14], loss of reduction [15,16], injury of triangular fibrocartilage complex [17], or wrist pain [18,19]. To the best of our knowledge, no studies have been reported about postoperative RJS.…”
Section: Introductionmentioning
confidence: 99%